Strategy of Knowledge and Intellectual Capital Management - Kubiak, Bernard F. (Advanced Information Technologies for Management – AITM 2009, 2009)
The article presents evaluation of the condition and possibilities of developing and implementing the knowledge management strategy in Polish organizations with the use of intelligent IT solutions and tools. The key role of intellectual capital and intellectual assets has been emphasised. Much attention has been paid to the methods and tools of identifying and meeting information-related needs of decision-makers at all management levels in organizations in the period of economic slowdown. The urgent need of implementing a cohesive analytical environment and a non-investment service model of IT solutions and infrastructure functionality, including Cloud Computing and Software- as-a-Service has been pointed out. Moreover, attention has been paid to the necessity of developing and implementing strategies of the competent intellectual capital use of analytical outcomes in business processes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 160-169